2010
DOI: 10.1016/j.juro.2009.08.111
|View full text |Cite
|
Sign up to set email alerts
|

Repeat Synthetic Mid Urethral Sling Procedure for Women With Recurrent Stress Urinary Incontinence

Abstract: A repeat synthetic mid urethral sling procedure has a significantly lower cure rate than a primary mid urethral sling procedure. The repeat retropubic approach has a higher success rate than the repeat transobturator approach. The incidence of de novo urgency and urge incontinence are significantly higher in repeat procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 17 publications
4
86
1
1
Order By: Relevance
“…To prevent the movement of urethra and support urethra against increased abdominal pressure, polyprolen mesh is placed in the obturator foramen in TOT procedure with a route of the trocar that avoid potential complications as bladder, bowel and vessels injuries (16). Stav et al demonstrated a 86% success rate after TOT surgery in their series of 1225 patients (17). Some surgeon reported up to 91% cure rate after one year follow up (18).…”
Section: Discussionmentioning
confidence: 96%
“…To prevent the movement of urethra and support urethra against increased abdominal pressure, polyprolen mesh is placed in the obturator foramen in TOT procedure with a route of the trocar that avoid potential complications as bladder, bowel and vessels injuries (16). Stav et al demonstrated a 86% success rate after TOT surgery in their series of 1225 patients (17). Some surgeon reported up to 91% cure rate after one year follow up (18).…”
Section: Discussionmentioning
confidence: 96%
“…The authors later reported a 3-year follow-up of this study in which 20 % of the transobturator group underwent repeat surgery compared with 1.4 % of the retropubic group [22]. Although repeat surgery is a very clinically relevant outcome measure, it is highly subject to physician biases and the potential bias in this study is that: 1) the physicians were not blinded to the initial surgical procedure; 2) they were already aware of their 6-month results suggesting that subjects with transobturator procedures were more likely to request repeat surgery; 3) and their salvage operation was a retropubic sling [23]. It is very likely that physicians would be more willing to perform a retropubic operation on someone who had a prior transobturator procedure than those who already had a retropubic sling.…”
Section: Evaluation Of Urethral Functionmentioning
confidence: 97%
“…Retropubic MUS however have been shown to be more effective than transobturator slings for recurrent SUI in patients who have failed a previous transobturator sling in recurrent SUI associated with ISD and following a Burch colposuspension [86,87].…”
Section: Management Of Recurrent Suimentioning
confidence: 99%
“…In a retrospective study of 1,225 women who underwent a MUS procedure with a mean follow-up of 5 years, Stav et al [87] reported a subjective success rate of 86% for primary sling versus 62% in the repeat-sling group (p <0.001). The repeat retropubic approach was significantly more successful than the repeat transobturator approach (71% vs. 48%, p = 0.04).…”
Section: Management Of Recurrent Suimentioning
confidence: 99%